2011
DOI: 10.1007/s00397-011-0605-7
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced crystallization of high-density polyethylene: the effects of shear and uniaxial extension

Abstract: The effects of shear, uniaxial extension and temperature on the flow-induced crystallization of two different types of high-density polyethylene (a metallocene and a ZN-HDPE) are examined using rheometry. Shear and uniaxial extension experiments were performed at temperatures below and well above the peak melting point of the polyethylenes in order to characterize their flow-induced crystallization behavior at rates relevant to processing (elongational rates up to 30 s −1 and shear rates 1 to 1,000 s −1 depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 58 publications
(62 reference statements)
5
27
2
Order By: Relevance
“…Both Derakhshandeh and Hatzikiriakos (2012) and White et al (2012) also observed the viscosity upturn at constant strain in extensional flow. Derakhshandeh and Hatzikiriakos (2012) performed experiments on two grades of high-density polyethylene of which Ansari et al (2010) studied the rheology.…”
Section: Continuous Extensional Flowmentioning
confidence: 84%
See 2 more Smart Citations
“…Both Derakhshandeh and Hatzikiriakos (2012) and White et al (2012) also observed the viscosity upturn at constant strain in extensional flow. Derakhshandeh and Hatzikiriakos (2012) performed experiments on two grades of high-density polyethylene of which Ansari et al (2010) studied the rheology.…”
Section: Continuous Extensional Flowmentioning
confidence: 84%
“…Derakhshandeh and Hatzikiriakos (2012) performed experiments on two grades of high-density polyethylene of which Ansari et al (2010) studied the rheology. As the onset of the terminal regime is not shown, we are not able to estimate the longest relaxation times.…”
Section: Continuous Extensional Flowmentioning
confidence: 99%
See 1 more Smart Citation
“…Next to shear, also extension in flow has been shown to be capable of generating first higher nuclei and—at higher stresses—oriented structures both for PP and for HDPE . In contrast to the rheological concept of “weak” (shear‐dominated) and “strong” (extension‐dominated) flows, comparable levels of work input to a system were found to give comparable effects in shear and extension by Stadlbauer .…”
Section: Processing‐based Modificationsmentioning
confidence: 99%
“…Such studies have been performed on, for example, isotactic polypropylene (iPP) (Housmans et al 2009;Ma et al 2011;Lamberti et al 2007;Vleeshouwers and Meijer 1996), polyethylene (PE) (Carrot et al 1993;Derakhshandeh and Hatzikiriakos 2012), isotactic poly(1-butene) (iP1B) (Acierno et al 2008;Hadinata et al 2007;Hadinata et al 2005;Roozemond and Peters 2013), and poly(lactic acid) (PLA) (Fang et al 2013), either using the short-term shear protocol (Liedauer et al 1993), cf. refs.…”
Section: Introductionmentioning
confidence: 99%